INTONATION STRUCTURE OF ENGLISH - Muzaffarova Sevinch; Sattorova Sabohat; Husniddinova Ozoda (TADQIQOTLAR, 2025)
Abstract   This article explores the structure of intonation in English and its significance in effective communication. It highlights key features of intonation, such as  pitch  variation,  stress,  emphasis,  and  boundary  tones,  demonstrating  how  these elements contribute to meaning and emotional expression. The article emphasizes the importance  of  mastering  intonation  to  improve  fluency  and  listening  skills.  It  also discusses how intonation patterns can vary across cultures and regions and suggests methods  for  improving  intonation  through  consistent  practice  and  exposure  to authentic  English.  Overall,  the  article  provides  insights  into  the  complexity  of intonation and its role in English communication.